ADAMTS7, a target in atherosclerosis, cooperates with its homolog ADAMTS12 to protect against myxomatous valve degeneration - Timothy J. Mead; Sumit Bhutada; Niccolò Peruzzi; Janet Adegboye; Deborah E. Seifert; Elisabeth Cahill; Jeanne Drinko; Eoin Donnellan; Anu Guggiliam; Zoran Popovic; Brian Griffin; Karin Tran-Lundmark; et al. (Journal of Molecular and Cellular Cardiology Plus)
The physiological roles of the metalloprotease-proteoglycan ADAMTS7, a drug target in atherosclerosis and vascular restenosis, and its homolog ADAMTS12, are undefined in the cardiovascular system. The objective of the present work was to investigate their roles in mice with genetic inactivation of both proteases and in relation to the resulting valve defects, to define their proteolytic activities in the matrisome. Here, we demonstrate that Adamts7 and Adamts12 are co-expressed in heart valves and each buffers inactivation of the other by compensatory upregulation. Leaflets of Adamts7−/−;Adamts12−/− aortic valves, but not the respective single mutants, were abnormally shaped at birth, with progressively severe disorganization and enlargement occurring thereafter. Doppler echocardiography showed that Adamts7−/−;Adamts12−/− mice had stenotic and regurgitant aortic valves. We investigated ADAMTS7 and ADAMTS12 substrates relevant to the valve matrisome in secretome libraries from Adamts7−/−;Adamts12−/− cells using the N-terminomics technique Terminal Amine Isotopic Labeling of Substrates (TAILS). Although ADAMTS7 and ADAMTS12 shared several extracellular matrix (ECM) substrates, cleavage sites and sequence preference for each protease were distinct. Adamts7−/−;Adamts12−/− valve leaflets showed accumulation of several of the identified ECM substrates, including periostin, a matricellular protein crucial for cardiac valve homeostasis. We conclude that the myxomatous degeneration in Adamts7−/−;Adamts12−/− valve leaflets reflects a complex disturbance of ECM proteostasis with accumulation of multiple ADAMTS7 and ADAMTS12 ECM substrates, and perturbation of regulatory pathways with roots in ECM, such as TGFβ signaling, which was increased in the mutant valves.